S04.2 New diagnostics for syphilis and yaws and detection of haemophilus ducreyi in cutaneous lesions in children. (13th September 2015) - Pillay, Allan; Chi, CH; Kwakye, C; Danavall, D; Taleo, F; Katz, S; Lahra, M; Tun, Y; Ballard, RC; Asiedu, K; Chen, CY
Abstract : Introduction: We evaluated a multiplex PCR assay that can distinguish between syphilis and yaws on children with cutaneous lesions. Also, a rapid syphilis test, Chembio DPP Screen and Confirm Assay was evaluated for serological diagnosis of yaws. Methods: Lesions swabs for PCR were obtained from children (5–14 years old) in West Akyem Municipality, Ghana pre- and post-MDA with azithromycin and pre-MDA on Tanna Island, Vanuatu. DPP testing was done on site and blood was collected for serology (RPR and TPPA). Molecular diagnosis and screening for azithromycin resistance markers was done using TaqMan-based real-time multiplex PCR tests. Another duplex PCR test was used to detect H. ducreyi and M. ulcerans. Results: Pre-MDA TPPA and RPR dual positivity was 35.8% (63/176) in Vanuatu and 33.6% (109/326) in Ghana and post-MDA was 18.6% (16/43) and 6.5% (3/46), respectively in children with skin lesions. The overall sensitivity and specificity of the DPP treponemal component versus TPPA was 88.2% and 82.7%, and DPP non-treponemal component versus RPR was 84.8% and 94.7%. In children with T. pertenue PCR-positive lesions, dual positive DPP had an overall sensitivity and specificity of 86.3% and 78.6%, and a PPV of 44% and a NPV of 96.7%. 14.9% (27/181) of pre-MDA swab samples from Vanuatu and 17.3% (31/179) in Ghana were PCR-positive for T. pertenue . None of the 49 samples from Ghana were positive for T. pertenue post-MDA. Azithromycin resistance markers were not found in any of the samples. H. ducreyi was detected by PCR in 40.3% (73/181) of samples from Vanuatu, and 27.4% (51/208) from Ghana pre-MDA and 28.6% (14/49) in Ghana post-MDA. Six children were co-infected with T. pertenue and H. ducreyi in Vanuatu and seven in Ghana. M. ulcerans was not detected. Conclusion: The DPP test is a useful screening test to exclude yaws in cases with a high index of suspicion on clinical grounds and the real-time PCR is essential for confirmation of a yaws diagnosis. MDA with oral azithromycin is effective for treatment of yaws but has limited impact on H. ducreyi .